(untitled) (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Tumor necrosis factor related-apoptosis-inducing ligand (TRAIL) is a powerful and selective activator of apoptosis in many cancer cells. We aim to investigate the expression and significance of TRAIL death receptor DR4 and DR5 in pancreatic cancer (PC) tissues. Method: Twenty-eight histologically verified samples of PC tissue were collected between 2018 and 2019. TRAIL death receptor expression profiles were determined by immunohistochemistry. Result: Death receptor DR4 and DR5 were expressed in the PC tissue and the adjacent non-cancerous pancreatic tissues, the expression of DR4 and DR5 in the PC tissue was significantly higher than that of the adjacent non-cancerous pancreatic tissues (p<0.05). Additionally, in both the tissue group, the expression of DR4 was significantly stronger than the DR5 (p<0.05). To assess the relationship between DR4 and DR5 expression, differentiation, and tumor staging of PC, the result reveals that the expression of DR4 and DR5 was significantly higher in stage I tumors than the stage II, III, IV tumors (p<0.05). In contrast, the expression of DR4 and DR5 was decreased with a decrease in the degree of differentiation of tumors. However, the difference was not statistically significant. Conclusion: The membrane expression of TRAIL death receptor DR4 and DR5 is greater in PC than in the adjacent non-cancerous pancreatic tissues. Furthermore, increased membrane expression of TRAIL death receptor DR4 and DR5 in stage I PC and well-differentiated PC may predict the prognosis and feasibility of using TRAIL gene therapy as a treatment option for early PC.